Sperm morphology and testicular histology of the polyandric species Leptodactylus podicipinus (Anura: Leptodactylidae) from an urban environment - Bordin, Rafael Oliveira; Fernandes, Carlos Eurico dos Santos; Franco-Belussi, Lilian; Leão, Taynara Ribeiro Farias [UNESP]; Sanabria, Marciana (Wiley, 2022)
Anurans have a high reproductive diversity, which is closely associated with testicular dynamics and sperm production. This variety in reproduction is modulated by the sexual characteristics of reproductive strategies, such as polyandry. Leptodactylus podicipinus has high reproductive plasticity, wide geographical distribution, and polyandric behavior. Although aspects of the testes and sperm of this species are known, knowledge about the relationship between these aspects and reproductive investment is scarce. The present study evaluated the morphological characteristics of the testes and sperm in an urban environment. We used 11 sexually mature males from the city of Campo Grande, Mato Grosso do Sul, Brazil. The specimens were obtained from night excursions between April and September, the months that constitute the post-rainy season. The biometric data (snout-vent length, testes, and body mass) were associated with sperm parameters (length of the spermatozoon head and tail). Stereological analyses of sperm morphology and the testes were performed. The results showed correlations between testis mass and spermatozoon length, which were positively related to head length and negatively related to tail length. The locular area and tail length were also negatively correlated. The percentage of normal spermatozoa was 97%; however, some sperm heads and tails exhibited different morphologies from the pattern described for the species. The germinative structure comprised more than 50% of the locular area composed of spermatozoa. The results of this study contribute to the knowledge of aspects related to the reproductive biology of L. podicipinus obtained from an urban environment.
Keywords: amphibians; germ cells; male gonad; spermatogenesis; testicular morphology